Legal certainty of land certificate letter (Surat Keterangan Tanah or SKT) in land sale and purchase transactions as proof of ownership - Muhammad Viegri; Muhammad Tahir (Privietlab, 2026)
This study examines the legal certainty of the Land Certificate Letter (Surat Keterangan Tanah/SKT) in land sale and purchase transactions as proof of ownership. This study aims to analyze the legal status, evidentiary value, and level of legal certainty of SKT use in land transactions. A normative juridical approach was used, employing statutory, conceptual, and case-based analyses of the relevant literature. The results reveal that the SKT serves only as administrative proof of physical land possession and not as legal proof of ownership. The SKT provides prima facie evidence that can be used to register land ownership but does not ensure full legal protection. To guarantee legal certainty, SKT-based transactions must be followed by an official deed of sale before a Land Deed Official (PPAT) and land registration at the National Land Agency (BPN). This aligns with the legal principles of certainty (rechtszekerheid) and legal protection (rechtsbescherming) under the Indonesian Agrarian Law (UUPA) and Government Regulation No. 24 of 1997.